Factores de riesgo y señales de alarma en pacientes con Dengue atendidos en el Hospital Minsa II -2 Tarapoto, Mayo-Octubre 2016 - Quispe Diaz, Fanny Smith (2016)
The objective of this research was to determine the risk factors and alarm signals in dengue patients treated at the MINSA II - 2 Tarapoto Hospital, from May to October 2016. The type of investigation was considered as non - experimental, quantitative, descriptive Of cross-section with data collection retrospective. The sample consisted of 43 clinical histories, which met the inclusion and exclusion criteria. The instrument for collecting the data was a record sheet of data, which they obtained from the medical records. The results were: dengue patients treated at the MINSA II - 2 Tarapoto Hospital presented the following: social risk factors, 14% without water service and 33% without a trash removal service. In environmental risk factors 100% recognize climate change as a contributing problem to the disease. The biological risk factors 37% correspond to the age group of 20 to 29 years, 56% are male, 100% did not have dengue antecedents and the anti-yellow fever vaccine was not used as a prevention. The alarm signals were general malaise 93%, followed by fever 79% and headache / headache 67%. In conclusion: the type of diagnosis of dengue in patients attended at the MINSA II - 2 Tarapoto Hospital was dengue with no sign of alarm 67% followed by dengue with alarm sign with 33%.